2010
DOI: 10.1586/egh.10.72
|View full text |Cite
|
Sign up to set email alerts
|

Risk of morbidity in contemporary celiac disease

Abstract: Celiac disease is one of the most common chronic diseases encountered in the Western world with a serological prevalence of approximately 1%. Since it is so common, much comorbidity will occur either as associations or simply by chance, or as complications of the disorder. Many of the published studies purporting to establish the frequency of these occurrences have been limited by factors such as the source and number of patients considered, choice of control groups and ascertainment bias. Recent epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 171 publications
1
19
0
Order By: Relevance
“…With a serological prevalence of 1% ∼524 000 individuals should be present in the UK population These results inform the structure of the coeliac iceberg particularly with regard to the ratio between diagnosed and undiagnosed patients with CD. 27 Several groups have addressed the question whether there is a relationship between the prevalence of CD and socioeconomic status but reviewed results are conflicting. 28 For example, in a study of children from South Wales, CD was more common in higher socioeconomic populations, 29 and this was confirmed in a recent large study from the UK, 28 but was not found in an investigation from Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…With a serological prevalence of 1% ∼524 000 individuals should be present in the UK population These results inform the structure of the coeliac iceberg particularly with regard to the ratio between diagnosed and undiagnosed patients with CD. 27 Several groups have addressed the question whether there is a relationship between the prevalence of CD and socioeconomic status but reviewed results are conflicting. 28 For example, in a study of children from South Wales, CD was more common in higher socioeconomic populations, 29 and this was confirmed in a recent large study from the UK, 28 but was not found in an investigation from Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study showed that celiac disease is not associated with an increased risk of colorectal neoplasia (53). A recent review suggests that cancer risks are lower than was once thought (54).…”
Section: Davis' Point -Celiac Patients Show Increased Cancer Ratesmentioning
confidence: 98%
“…It is estimated to affect 1 in 100 people worldwide; 2.5 million Americans are undiagnosed and are at risk for long-term health complications [1]. Two to eight percent of patients with type 1 diabetes mellitus also have CD, and it also occurs with increased frequency in patients with Down's syndrome, Hashimoto's thyroiditis, Irritable Bowel Syndrome (IBS) and in the people with Irish, Punjabi and other South Asian ethnic backgrounds [2].…”
Section: Introductionmentioning
confidence: 99%